2018
DOI: 10.1016/j.humpath.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

PD-1, PD-L1, and CD163 in pancreatic undifferentiated carcinoma with osteoclast-like giant cells: expression patterns and clinical implications

Abstract: Undifferentiated carcinoma with osteoclast-like giant cells (UCOGC), a variant of pancreatic ductal adenocarcinoma (PDAC), has a striking genetic similarity to PDAC but a significantly improved overall survival. We hypothesize that this difference could be due to the immune response to the tumor, and as such, we investigated the expression of PD-1, PD-L1, and CD163 in a series of UCOGC. To this aim, 27 pancreatic UCOGCs (11 pure and 16 PDAC-associated), 5 extrapancreatic tumors with osteoclast-like giant cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 34 publications
2
51
1
Order By: Relevance
“…The literature search identified globally 158 unduplicated articles, 126 of which were excluded after reviewing their title/abstract, which left 32 articles eligible for full text review. After applying our inclusion and exclusion criteria, 18 articles (for 17 cohorts) were selected for this systematic review [7,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] (supplementary Figure S1, available at Annals of Oncology online).…”
Section: Relationships Among Msi Pd-1/pd-l1 Expression and Tmb In Camentioning
confidence: 99%
See 3 more Smart Citations
“…The literature search identified globally 158 unduplicated articles, 126 of which were excluded after reviewing their title/abstract, which left 32 articles eligible for full text review. After applying our inclusion and exclusion criteria, 18 articles (for 17 cohorts) were selected for this systematic review [7,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] (supplementary Figure S1, available at Annals of Oncology online).…”
Section: Relationships Among Msi Pd-1/pd-l1 Expression and Tmb In Camentioning
confidence: 99%
“…The vast majority of the cohorts reported data on patients from the USA, followed by Asian and European subjects. The majority of the manuscripts (59%) investigated original cohorts of patients [7,61,[63][64][65][66][67][68][69][70]75], whereas data derived from external (public or private) databases were used in some papers [59,62,[71][72][73][74].…”
Section: Relationships Among Msi Pd-1/pd-l1 Expression and Tmb In Camentioning
confidence: 99%
See 2 more Smart Citations
“…Different antibodies and sets of assay condition for PD-L1 have been used for respective immune checkpoint inhibitors with contrasting results [20,21], while the most used clone for PD-L1 is SP142 [11]. Luchini et al used clone E1L3N for PD-L1 IHC in above mentioned study [19], whereas we used 22c3 which is approved to aid in selection of patients for pembrolizumab treatment based on PD-L1 expression in FFPE tumor samples [22]. It is reported that 22c3 was prone to show lower mean score of PD-L1 expression in IHC for NSCLC compared to E1L3N [21], therefore it is unlikely that our results of PD-L1 high expression in IHC was false positive.…”
Section: Discussionmentioning
confidence: 99%